2020
DOI: 10.3390/vaccines8020182
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Membrane Vesicle Vaccine Augments the Efficacy of Anti-PD1 Antibody in Immune Checkpoint Inhibitor-Resistant Squamous Cell Carcinoma Models of Head and Neck Cancer

Abstract: Immune checkpoint inhibitor (ICI) immunotherapy improved the survival of head and neck squamous cell carcinoma (HNSCC) patients. However, more than 80% of the patients are still resistant to this therapy. To test whether the efficacy of ICI therapy can be improved by vaccine-induced immunity, we investigated the efficacy of a tumor membrane-based vaccine immunotherapy in murine models of HNSCC. The tumors, grown subcutaneously, are used to prepare tumor membrane vesicles (TMVs). TMVs are then incorporated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…[9][10][11] TMVs containing GPI-ISMs have been shown to induce immunity in murine thymoma, 11 breast cancer, 9 12 and head and neck cancer. 13 Since these TMV vaccines contain the unique antigenic signature of each individual tumor, the platform provides an opportunity to deliver a personalized vaccine immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] TMVs containing GPI-ISMs have been shown to induce immunity in murine thymoma, 11 breast cancer, 9 12 and head and neck cancer. 13 Since these TMV vaccines contain the unique antigenic signature of each individual tumor, the platform provides an opportunity to deliver a personalized vaccine immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…TMV-mediated immunotherapy has been shown to be a potential enhancer of immunosuppressants for the treatment of metastatic triple-negative breast cancer. Bommireddy et al 144 found the same effects of TMV vaccines in a mouse model of head and neck squamous cell carcinoma (HNSCC). They also found that the TMV vaccines could effectively inhibit tumor growth in MOC1 and MOC2 murine oral cancer models and cooperate with anti-PD1 to prolong the survival time of tumor-bearing mice.…”
Section: Clinical Applications Of Tmvsmentioning
confidence: 84%
“…The findings suggest the prospect of a personalized therapeutic vaccine for HNSCC. The application of surgically removed tumor tissue to prepare TMV for the production of a personalized vaccine for individual patients in future clinical practice (Bommireddy et al, 2020).…”
Section: Personalized Antigen Vaccinesmentioning
confidence: 99%